Eksistensi Pengawasan Dan Pelayanan Bea Dan Cukai Di Perairan Laut Teritorial Aceh Barat Dalam Kasus Rokok Ilegal - Ria Agustina; Nila Trisna (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
West Aceh with its vast sea brings good benefits to the community, the natural resources contained in the sea are very abundant, so that they can be utilised for the welfare of the community. With a very large sea zone, West Aceh is vulnerable to the criminal act of smuggling illegal cigarettes. One of the criminal offences that occurred was the smuggling of illegal cigarettes. The formulation of the problem in this study is how the Supervision of the Meulaboh Customs and Excise Supervision and Service Office (KPPBC) in supervising the smuggling of illegal cigarettes and what are the factors that become obstacles for the Meulaboh Customs and Excise Supervision and Service Office (KPPBC) in conducting supervision of illegal cigarettes. The purpose of this study is to determine the Supervision of the Office of Customs and Excise Supervision and Services (KPPBC) Meulaboh in supervision of the smuggling of Illegal Cigarettes and to find out also the factors that become obstacles in conducting supervision of the smuggling of Illegal Cigarettes. This research is included in the type of empirical legal research. The results of this study are that the supervision carried out on the circulation of illegal cigarettes without excise until now is still widespread in the Meulaboh area, which handles excisable goods or illegal excise that has entered into the Meulaboh area, namely the Section Head of Enforcement and Investigation, as well as Factors that become obstacles for the Office of Customs and Excise Supervision and Services (KPPBC) Meulaboh in conducting supervision of illegal cigarettes, namely the Lack of Patrol Officer Personnel, Large Geographical Area, Economic Factors, Still weak supervision carried out by customs and excise officers and the lack of operational facilities.